Do teachers differ in terms of their empathy toward liked students and disliked students? The role of empathic motivation - Wang, Xia; Shuangguan, Chenyu; Huang, Yuesheng (Frontiers in Psychology, 2025)
IntroductionTeacher empathy has been proven to be highly relevant to both the educational process and outcomes. Therefore, exploring its influencing factors and developing effective cultivation strategies are highly importance. The present study aimed to examine the effects of teacher-perceived student likability on teacher empathy and to further explore the role of empathy motivations.MethodsIn Study 1, 138 primary and secondary school teachers (mean age = 38.0 ± 8.8 years) reported their anticipated emotional exhaustion, empathic motivation, and empathic reaction when they read a text that described a negative event involving either a disliked or liked student. In Study 2, another 221 primary and middle school teachers (mean age = 34.8 ± 10.1 years) took part in an intervention designed to activate empathic motivation.ResultsThe results of study 1 showed that teachers felt less empathy in the former context. In addition, anticipated emotional exhaustion and empathic motivation serially mediated the effect of teacher-perceived student likability on teacher empathy. The results of Study 2 showed that teachers' empathy toward disliked students improved and that the likable empathy bias was eliminated when empathic motivation was primed.DiscussionThese findings suggest that empathic motivation plays a crucial role in likable empathy bias among teachers in that it not only functions as a key mechanism underlying this bias but also emerges as a potential pathway for mitigating such bias. Our research has important theoretical and practical significance.